A construção da narrativa em textos produzidos por estudantes com e sem TDAH - Renata Amaral de Matos Rocha (2018)
The main goal of this research was to have the performance of ADHD (Attention Deficit Hyperactivity Disorder) middle school students verified, together with non-ADHD students, who presented a high level of attention, comparatively, in their narrative text productions when offered the same conditions for that. In the scope of text production, we analyze some aspects of its construction and organization, such as: narrative structure, perception of elements of a text, reference, thematic unit, textual progression, communicative purpose, informative relevance and relationship between texts. Our purpose was to compare the performance of these two groups to explore possible differences in performance between them and to seek evidence that can explain these differences. Thus, we try to answer these questions: is the linguistic performance of ADHD students inferior to that of students with a high level of attention? To what extent can attention deficit contribute to a poor language performance of ADHD people? The initial hypothesis of this research is that students with this disorder tend to have a less efficient linguistic performance in their written productions than students with a high level of attention, even though they are offered identical production conditions. This hypothesis has its origin in the premise that there is a notable relation between language and attention. However, we have evidence that performance of the two groups presents differences, but that they do not indicate that the performance of the experimental group is specifically inferior in relation to the control group. In this perspective, we outline that the general objective of this work is related to the investigation of linguistic performance of ADHD and non-ADHD students in the production of their written narrative texts and in the verification of possible differences of performance between these groups of students. To achieve this, we adopted some methodological procedures related to quasiexperimental research and linked them to qualitative and quantitative research approach. Data was collected in a public school, located in Belo Horizonte, Minas Gerais. Eighteen students were selected to participate in data collection. This group of students was organized in two working groups (experimental, GET, and control, GCA). The texts the students wrote compose the corpus of this research and constitute our locus of observation. The analysis was based on theories that consider the text as “an original linguistic phenomenon”, as “necessary form” of occurrence of verbal communication, according to Antunes (2010). And, also, theories that understand that “a text is a communicative event in which linguistic, cognitive and social actions converge” (BEAUGRANDE, 1997, p.10) and assume that “all texts are multimodal. The language always has to be realized through, and comes accompanied by, other semiotic modes” (KRESS and VAN LEUWEEN, 1998, p. 186, apud RIBEIRO, 2013, in free translation of this author). Thus, we understand that a person's linguistic performance can only be evaluated by his ability to act through discourse, in different social situations, to reach his communicative goals. This research is basically based on literature about ADHD (BARKLEY, 2008, DUPAUL, 2007, DSM-5) and studies on text and language practices (BEAUGRANDE, 1997, ANTUNES 2010, BRONCKART, 1999), and it is based on the narrative structure proposed by Labov and Waletsky (1968) and Labov (1972). Results show that there are differences in performance among the groups of informants in the production of written text. However, evidence does not confirm our initial hypothesis that there is a tendency for ADHD patients to have an inferior linguistic performance, especially when we investigate some aspects of construction and textual organization. When analyzing texts of students of each group, we find that in some aspects, GCA performance is better than GET performance, but in others, GET performs better; and there is also similar performance in some other aspects analyzed. We are faced with indications that invoke important reflections on ADHD children and teenagers and on the stigma they carry in the various social spaces in which they are inserted, one of them, the school.